Phatic Strategies Used in Conversational Opening by American and Vietnamese Staff and Managers in American and Vietnamese Movies - Hoang Tra My, (Tạp chí Khoa học Xã hội và Nhân văn (VNU Journal of Social Sciences and Humanities), 2025)
To open a conversation, parties often follow sequences or phases including summons-answer, greeting, phatic communion, and topic initiation. Parties need certain strategies to accomplish these sequences. The present study aims to find out and describe English and Vietnamese phatic communion strategies in conversational openings based on 214 English and 197 Vietnamese staff-manager conversations collected from movies. The data is coded manually with the method of qualitative content analysis. The findings indicate that the American and Vietnamese parties share more similarities than differences in deploying phatic strategies. Regarding similarities, in both languages, phatic strategies occur frequently and rather equally, functioning as a polite way to help parties raise a topic of concern smoothly and foster participants’ social relationships. As to differences, the Vietnamese parties prefer positive politeness strategies to express their concern or regards on their interlocutors whereas the American parties like negative politeness strategies to minimize their imposition on their interlocutors.    Received 14th March 2018; Revised 18th June 2018; Accepted 20th October 2018